2015
DOI: 10.1186/s12937-015-0066-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the nutrient content of children’s menu items at US restaurant chains, 2010–2014

Abstract: ObjectiveTo determine changes in the nutritional content of children’s menu items at U.S. restaurant chains between 2010 and 2014.MethodsThe sample consisted of 13 sit down and 16 fast-food restaurant chains ranked within the top 50 US chains in 2009. Nutritional information was accessed in June-July 2010 and 2014. Descriptive statistics were calculated for nutrient content of main dishes and side dishes, as well as for those items that were added, removed, or unchanged during the study period.ResultsNutrient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 17 publications
(19 reference statements)
3
25
0
1
Order By: Relevance
“…Results from this study are similar to findings from Deierlein and colleagues, 12 who examined nutritional differences in children's entrées and side dishes available for sale in 29 of the top 50 chain restaurants in 2010 and 2014. Consistent with current findings, the authors reported no significant differences in calories, sodium, or saturated fat in children's main dishes or side dishes offered at fast-food restaurants from 2010 to 2014.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Results from this study are similar to findings from Deierlein and colleagues, 12 who examined nutritional differences in children's entrées and side dishes available for sale in 29 of the top 50 chain restaurants in 2010 and 2014. Consistent with current findings, the authors reported no significant differences in calories, sodium, or saturated fat in children's main dishes or side dishes offered at fast-food restaurants from 2010 to 2014.…”
Section: Discussionsupporting
confidence: 85%
“…10,11 A recent study of children's entrées and side dishes in 29 chain restaurants found that in 2014, one third of main dishes at fast-food restaurants and half of main dishes at full-service restaurants exceeded levels of calories, fat, saturated fat, and sodium recommended by the 2010 Dietary Guidelines for Americans. 12 The nutrient content of children's beverages and desserts—two of the four largest contributors to added sugars and solid fats in children's restaurant food—were not assessed. Further, no recent studies have assessed whether changes in nutritional quality of restaurant menu items have occurred since the start of programs like Kids LiveWell and other voluntary restaurant commitments.…”
Section: Introductionmentioning
confidence: 99%
“…According to the results, the energetic contribution of meals intended for school-age children are above the nutritional recommendations for these meals. The estimations are consistent with some research studies done in the United States [18,20,21] and in Monterrey and Mexico cities [22].…”
Section: Discussionsupporting
confidence: 92%
“…16,17 Researchers have reported that restaurant meals for children, adolescents and also adults were typically too energy dense, contained too much fat 18,19 and too much sodium. 20,21 Adolescents have also been reported to consume more sugar sweetened beverages (SSB) when eating in a restaurant compared to the home. In an American study where fast food restaurants were scored on the Healthy Eating Index, children's meals scored higher than adult meals, however the overall quality of food was poor compared to dietary recommendations.…”
Section: Introductionmentioning
confidence: 99%